Peran Travel Consultant dalam Penjualan Tiket Perjalanan dalam Negeri di Anta Express - Agoes, Adrian; Firdaus, Azhar (Manajemen dan Pariwisata, 2024)
The tourism industry in Indonesia has experienced significant growth, particularly following the post-COVID-19 recovery and the rise of the creative economy. As the sector rebounds, travel agencies play a crucial role in facilitating domestic ticket sales and travel packages. Traditional travel agencies, such as PT Anta Express Tour & Travel, face competition from online booking platforms, which calls for a study on the unique value offered by travel consultants in enhancing customer experiences and the sales process. This study aims to explore the role of travel consultants at PT Anta Express Tour & Travel in domestic travel ticket sales. Using a qualitative research approach, data was gathered through direct observation, semi-structured interviews, and a review of relevant literature. The findings highlight four key roles played by travel consultants: providing personalized advice and recommendations, managing bookings, resolving issues, and delivering customer service. Additionally, three main reasons were identified for why customers still prefer using travel consultants: convenience, access to exclusive offers, and ongoing support during the trip. The study concludes that travel agencies can maintain their competitiveness by focusing on personalized services that appeal to specific customer segments, particularly those who value professional advice and human interaction in their travel planning. Therefore, traditional and online booking channels can coexist in the future, serving different market needs.